(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article highlights some aspects of the professional training of social pedagogues for working with "risk groups" adolescents, in particular, in terms of forming constructive interaction skills and positive life experiences in them; the author also highlights the issues of mastering the future specialists of the methodology of carrying out social pedagogical training with this category of children. The concept of "adolescents of the risk group", "training", "socio-pedagogical training" is specified. Particular attention is paid to the coverage of the content of socio-pedagogical training in the system of vocational training of social teachers.